Comparison of effectiveness and safety of ketamine with midazolam against higher dose of ketamine as procedural sedation for lumbar puncture in paediatric leukaemic patients - Faisal, Ahmed (2011)
INTRODUCTION: Children with leukaemia undergo several invasive procedures. Sedation is used to make these procedures more comforting to the patient as it is necessary for successful outcome. However sedatives can have devastating effects. In our centre as well as others, combination of ketamine with midazolam has been used for years without specific protocol. OBJECTIVE: To compare the effectiveness and safety of combination ketamine and midazolam against higher dose of ketamine as procedural sedation for lumbar puncture in paediatric leukemic patients. METHOD: A total of 29 paediatric leukaemia patients underwent 58 lumbar punctures in a double blinded crossover clinical trial. The 2 regimes compared were KM regime who received combined intravenous midazolam 0.1mg per kg with ketamine 1mg per kg against K2 regime who received higher dose of intravenous ketamine i.e. 2mg per kg. The main outcomes measured were time to achieve the desired sedation (Ramsay level of sedation at 6), time to complete lumbar puncture, time to regain consciousness (Aldrete recovery score of at least 8) and adverse effects. RESULTS: Twenty seven patients (93%) were successfully sedated with each of the regimens. Mean time taken for sedation and mean time to be fully conscious after sedation were significantly less (p value <0.05) in K2 regime. Mean time taken for sedation in K2 regime was 7.56 minutes (SD 4.4) and in KM regime it was 8.74 minutes (SD 3.6). Mean time to be fully conscious was 132 minutes (SD 93.5) for K2 regime while it took 173 minutes (SD 88.8) for patients in KM regime. There is no statistically significant difference in mean time taken to complete LP between the 2 regimes (P=0.06). Two patients in K2 regime developed tachycardia and one patient had pain after procedure while no patient in KM regimen had either of these. Five patients from either of the groups had desaturation. This was not statistically significant (McNemer Test 0.250) but it could be clinically relevant. Eight patients (30%) in KM regime required top-up doses of ketamine and 7 patients (26%) required top-up doses of ketamine in K2 regime. CONCLUSION: Ketamine as a sole agent is as effective and safe as combination of midazolam and ketamine. It should be considered in procedural sedation for lumbar puncture in paediatric leukemic patients. It has faster induction and reversibility but it cause more adverse reactions and do not reduce time taken for lumbar puncture. An initial dose of 2mg per kg is safe to be used with another top up dose of 0.5mg per kg. Top up doses are frequently required.